The Effect of Population, Percapita Expenditure and Inflation of Poverty in Aceh Province - Rahmat Alwiraq; Saharuddin (LPPM Universitas Malikussaleh, 2022)
This study aims to analyze the effect of Population, Per Capita Expenditures and Inflation on Poverty in Aceh Province. The independent variables are Population, Per Capita Expenditure and Inflation while the dependent variable includes Poverty. The data used in this research is secondary data for the period 2006-2021. The regression model used in this study is the multiple linear regression model. This study uses classical assumption tests such as the normality test, heteroscedasticity test, autocorrelation test and multicollinearity test. The regression tool in this study used eviews10 software. Based on the results of the study, it shows that the total population has a positive and insignificant effect on poverty in Aceh Province. Per Capita Expenditure Has a Negative and Not Significant Effect on poverty in Aceh Province. Inflation has a positive and significant impact on poverty in Aceh Province, while for all variables Investment, Population Per Capita Expenditure and Inflation jointly affect poverty. The test results for the coefficient of determination show that there is a relationship between the independent variables and the dependent variable in this study of 53.44%, which means that the other 46.55% is influenced by other variables outside of this study.